Pengembangan Lembar Kerja Peserta Didik (LKPD) Elektronik Berbasis Pendekatan Konstruktivisme pada Materi Sistem Sirkulasi untuk Peserta Didik SMA - Suci Fajrina; Mades Fifendy; Asrul; Vega Ersalina; Relsas Yogica (Universitas Nusantara PGRI Kediri, 2023)
21st Century Learning requires educators to be able to develop teaching materials in accordance with ICT developments and the needs of students. Electronic LKPD based on a constructivism approach to circulation system material for high school students was developed to help students become more interested and active in learning, understand material easily, and show the process of absorbing information so as to create meaningful learning. The type of research used is development research using the Intructional Development Institute (IDI) model which has 3 stages, namely define, develop, and evaluate. The subjects in this study were two lecturers of biologists at Padang State University, one biology educator and 30 students of class XI IPA at SMA Negeri 1 IV Koto. The object of this research is electronic LKPD based on constructivism approach on circulation system material for high school students. The research instruments used were educator interview questionnaires, student questionnaires, validity test sheets, and practicality test sheets. The results of the validity test of this electronic LKPD were 90.10% in the very valid category and the results of the practicality test of this electronic LKPD were 89.66% in the very practical category. It can be concluded that the electronic LKPD based on the constructivism approach on circulation system material for high school students gets very valid and very practical values.